Global Bioregionalisation of Invasive Angiosperms - Lorena Gali; Matheus Colli‐Silva; Alexandre Antonelli; Karina Fidanza (Journal of Biogeography, 2026)
Aim Understanding global patterns in plant invasions is critical for improving our understanding of plant biogeography and for informing conservation strategies. However, the bioregional structure of invasive angiosperms remains unresolved globally. Here, we delineate global bioregions of invasive angiosperms and assess how these regions differ in species traits and reported human uses. Location Global. Major Taxon Studied Invasive angiosperms belong to 48 orders and 184 families. Methods We compiled a global dataset of 3016 invasive angiosperm species from the Global Register of Introduced and Invasive Species (GRIIS). We generated species occurrence records and performed bioregionalisation using network clustering analyses in three independent runs, using the Infomap Bioregions software based on: (1) all available occurrences, (2) non‐native records and (3) invasive species. We then characterised the resulting bioregions using biological traits (life form, pollination, dispersal and propagation modes and photosynthetic pathway) obtained from global biodiversity repositories. Results We identify three consistent bioregion patterns from the non‐native occurrence dataset that directly reflect the distribution of invasive species outside their native ranges. These bioregions correspond to major latitudinal zones named here as Holarctic, Holotropical and Austral. The traits differ in terms of dominance from what was expected, which means that the bioregions may be selecting for the characteristics of the plants analysed there. The common dominant traits across all bioregions are C3 photosynthesis, insect pollination, seed propagation and medicinal use. Over‐ and underrepresented traits are recorded across all bioregions. The Holarctic bioregion generally exhibits strongly over‐represented characteristics; the Holotropical bioregion shows an over‐representation of human uses; and the Austral bioregion presents under‐represented characteristics. Main Conclusions Invasive angiosperms, despite having achieved their current global distributions primarily through anthropogenic activities that could have led to spatial homogenisation, exhibit structured bioregionalisation patterns. These findings suggest that invasion dynamics are controlled primarily by regional environmental constraints and species' traits, offering novel insights for conservation biogeography and the management of invasive species across biogeographic realms.

Scaling Laws Reveal a Unified Species‐Energy Relationship for Mountain Biodiversity - Zihan Jiang; Hongyan Liu; Zhiyao Tang; Jonathan M. Chase; Alexandre Antonelli; Michael Kessler; Maharaj K. Pandit; Kumar Manish; Wei Xu; Jianxiao Zhu; Qinggang Wang; Hang Sun; et al. (Global Ecology and Biogeography, 2026)
Aim Energy availability is often assumed to be a primary driver of variation in biodiversity across large‐scale environmental gradients such as elevation, but support for the role of energetic constraints is far from universal. Here, we assume that these variations in energy–richness relationships might arise from the degree of match between the scale of the response of organisms to energy (response scale) and the scale of the observation made (observation scale). Location 41 mountain ecosystems worldwide, with detailed case studies on Dongling Mountain, China. Time Period Contemporary. Major Taxa Studied Trees, shrubs, herbs, ferns, birds, ants, bees, Lepidoptera, Coleoptera, Orthoptera, soil fauna, litter‐layer fauna, bacteria, fungi. Methods First, we quantify the response scale on the basis of energy requirements, and then, we develop a general scaling model that explicitly describes how the scale matching between response and observation scale influences the predictive power of energy in determining elevational richness patterns; this model holds across taxonomic groups, trophic guilds, and ecosystems across mountains globally. Results Global analyses strongly supported the model's prediction that scale matching determines the detectability of energy‐richness relationships. On Dongling Mountain, energy availability best explained richness patterns at the predicted response scales for trees, herbs, and litter fauna. Main Conclusions Our model advances the understanding of montane biodiversity distributions by demonstrating the critical role of scale matching in energy–richness relationships. Our findings strongly support the existing mechanistic foundation for predicting biodiversity changes across spatial scales in montane ecosystems. The scale‐matching principle we identified is likely to be applicable to a wide range of taxa and other ecosystems where energy availability varies across scales.

Bioregionalisation of vascular aquatic macrophytes endemic to the Neotropical region - Adrian Cesar da Silva; Matheus Colli-Silva; Alexandre Antonelli; Karina Fidanza (Hydrobiologia, 2026)
The Neotropical region harbours the world’s highest diversity of endemic aquatic plants. Due to their diversity of lifeforms and dependency on aquatic environments for survival, these taxa may not exhibit a broad-scale biogeographic pattern consistent with hydrographic basins. Based on 90,409 occurrence records of 778 aquatic plant species endemic to the Neotropics, we delineated bioregions to evaluate regional connectivity and compared the resulting map with hydrographic basin boundaries. We then deployed spatial autoregressive models to test whether climatic heterogeneity (precipitation and temperature), topographic complexity, and paleoclimatic stability influenced bioregional boundaries. We identified 18 bioregions, whose limits did not coincide with hydrographic basins. Boundaries were instead linked to steep precipitation gradients and rugged terrain, highlighting their role as key drivers of Neotropical aquatic plant biogeography. Markov time analysis further identified the influence of physical barriers in driving bioregionalisation patterns. The mismatch between bioregions and river basins reflects distinct dispersal strategies and water dependency, underscoring the need for taxon-specific regionalisation. Phylogenetic inclusion confirmed that bioregions capture both taxonomic assemblages and evolutionary history, while rare-species weighting highlighted fine-scale areas as priorities for conservation. The integrative framework developed here advances our understanding of aquatic plant biogeography and provides valuable information to support wetland conservation.

Equipping the next generation of plant taxonomists: Insights and recommendations - Ana Rita G. Simões; Frederik Leliaert; Gemma L.C. Bramley; Ruth P. Clark; Rhian J. Smith; Manuel Luján; Ian Ondo; Matilda J.M. Brown; Gabriel K. Ameka; Catherine W. Lukhoba; Renata Borosova; Bente B. Klitgård; et al. (Trends in Plant Science, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Data-driven optimisation of national botanical garden systems for ex situ conservation - Yueling Zhan; Minhong Fan; Xian Yang; Xiaotian Pan; Miao Sun; Tuo Yang; Alexandre Antonelli; Zhiduan Chen; Jianfei Ye (Biological Conservation, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

The 30 by 30 biodiversity commitment and financial disclosure: metrics matter - Daniele Silvestro; Stefano Goria; Ben Groom; Thomas Sterner; Alexandre Antonelli (Current Opinion in Environmental Sustainability, 2025)

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Zoogeographical regions in the Atlantic Forest: patterns and potential drivers - Fernando Rodrigues da Silva; Anna Elizabeth de Oliveira‐Silva; Alexandre Antonelli; Ana Carolina Carnaval; Diogo B. Provete (Journal of Biogeography, 2024)
Aim To delineate present‐day zoogeographical regions of terrestrial vertebrates (frogs, lizards, snakes, birds and non‐volant mammals) in the Atlantic Forest. Within each taxonomic group, we examine the relative importance of abrupt climatic transitions, orographic barriers, past climate change and rivers in shaping zoogeographical boundaries. Location South America's Atlantic Forest. Methods We applied a network‐based method to delineate zoogeographical regions, using distribution data (range maps) for 455 species of frogs, 103 lizards, 220 snakes, 917 birds and 202 non‐volant mammals, in 50 × 50 km grid cells. We used hierarchical generalized linear mixed‐effects models to test environmental predictors associated with zoogeographical boundaries. Finally, we intersected the bioregion maps delineated for each group to identify general patterns across all vertebrates. Results We identified four zoogeographical regions for birds and snakes, and five for frogs, lizards and non‐volant mammals. Depending on the group, contemporary and past climate conditions, elevation variation and/or rivers were associated with zoogeographical boundaries. The combined maps indicate that the Atlantic Forest retains four spatially cohesive zoogeographical regions based on present‐day distribution of vertebrates. Main conclusions Cross‐taxon congruence indicates that the geographical and environmental characteristics of the Atlantic Forest have a strong influence on the location of zoogeographical regions for vertebrates. In contrast, transition zones appear to be associated with the spatial distribution of life history traits of each group, potentially explaining the observed differences in the number of bioregions across groups and the position of zoogeographical boundaries. This work paves the way for further research into the evolutionary assembly of the Atlantic Forest's zoogeographical regions and may help inform conservation priorities for maintaining their distinctive faunas.

Expert‐based range maps cannot be replicated using data‐driven methods but macroecological conclusions arising from them can - Heléne Aronsson; Alexander Zizka; Alexandre Antonelli; Søren Faurby (Journal of Biogeography, 2024)
Aim Answering many fundamental and applied scientific questions relies on accurate geographic range maps for species, such as those compiled by experts working with the International Union for Conservation of Nature (IUCN). However, these maps are resource demanding to produce and only available for a limited number of organisms. Here, we test to what extent standardized, data‐driven methods based on publicly available occurrences can reproduce expert‐based IUCN range maps and the macroecological conclusions drawn from them. Location Global. Time Period Present. Taxa Birds. Materials and Methods We estimated the geographic ranges for 7385 non‐marine bird species which either were non‐migratory or had spatially connected breeding and wintering ranges from publicly available, georeferenced point occurrences. We then quantified the spatial overlap between these range estimates and the IUCN expert‐derived range estimates. Finally, we compared global species richness patterns and the environmental correlates that emerge from both approaches. Results We find that range estimates based on point occurrence records overlap on average 52% with expert range estimates for the same species. The global species richness patterns estimated under both approaches are overall similar but show local and regional differences, for example, in the tropical Andes of northern South America and the Central Arc region of Africa. The estimated global drivers of richness are similar. Main Conclusions Expert‐derived estimates of species distributions are not reproducible by data‐driven approaches relying on currently available public records, even for well‐documented taxa such as birds. However, these discrepancies do not substantially change our macroecological understanding of global drivers of bird diversity.

Functional and historical drivers of leaf shape evolution in palms (Arecaceae) - Maria Fernanda Torres Jiménez; Nicolas Chazot; Thaise Emilio; Johan Uddling; Alexandre Antonelli; Søren Faurby; Christine D. Bacon (Global Ecology and Biogeography, 2023)
Aim Leaves display a remarkable variety of shapes, each with potential ecological advantages in specific climates. While the relations between leaf shape and either climate or height have been relatively well studied in eudicots, the macroecological drivers of shape remain poorly known in monocots. Here, we investigated the associations between climate and plant height with the evolution of leaf shape in a clade with high species and morphological diversity. Location Global. Time period Cretaceous to contemporary. Major taxa studied Palms (Arecaceae). Methods We apply a Bayesian phylogenetic mixed model to test for associations between climate and leaf shape (all – entire‐leaved, pinnate‐dissected, palmate‐dissected and costapalmate). We further reconstruct the ancestral leaf shape using multistate speciation and extinction models and compare the frequency of shapes with global temperatures through time. Results We find that plant height associates with dissected leaves and that annual precipitation associates with pinnate shapes. The ancestral leaf shape is unclear, but early diversification was dominated by pinnate‐dissected palms, which has remained the most species‐rich form of leaves throughout palm history. Main Conclusions Palms that are tall and live in humid regions are more likely to have pinnate leaves. Through geological time scales, temperature did not play an obvious role in determining leaf shapes. This study contributes to our understanding of how the diversity of leaf shapes is linked to biological and climatic factors.

Addressing chemical pollution in biodiversity research - Gabriel Sigmund; Marlene Ågerstrand; Alexandre Antonelli; Thomas Backhaus; Tomas Brodin; Miriam L. Diamond; Walter R. Erdelen; David C. Evers; Thilo Hofmann; Thorsten Hueffer; Adelene Lai; Joao P. M. Torres; et al. (Global Change Biology, 2023)
Climate change, biodiversity loss, and chemical pollution are planetary‐scale emergencies requiring urgent mitigation actions. As these “triple crises” are deeply interlinked, they need to be tackled in an integrative manner. However, while climate change and biodiversity are often studied together, chemical pollution as a global change factor contributing to worldwide biodiversity loss has received much less attention in biodiversity research so far. Here, we review evidence showing that the multifaceted effects of anthropogenic chemicals in the environment are posing a growing threat to biodiversity and ecosystems. Therefore, failure to account for pollution effects may significantly undermine the success of biodiversity protection efforts. We argue that progress in understanding and counteracting the negative impact of chemical pollution on biodiversity requires collective efforts of scientists from different disciplines, including but not limited to ecology, ecotoxicology, and environmental chemistry. Importantly, recent developments in these fields have now enabled comprehensive studies that could efficiently address the manifold interactions between chemicals and ecosystems. Based on their experience with intricate studies of biodiversity, ecologists are well equipped to embrace the additional challenge of chemical complexity through interdisciplinary collaborations. This offers a unique opportunity to jointly advance a seminal frontier in pollution ecology and facilitate the development of innovative solutions for environmental protection.

Multiple origins of mountain biodiversity in New Zealand's largest plant radiation - Anne Thomas; Heidi M. Meudt; Matthew J. Larcombe; Javier Igea; William G. Lee; Alexandre Antonelli; Andrew J. Tanentzap (Journal of Biogeography, 2023)
Aim How mountains accumulate species diversity remains poorly understood, particularly the relative role of in situ cladogenesis compared with colonization from lower elevations. Here, we estimated the contributions of in situ cladogenesis and colonization in generating biodiversity of a large mountain plant radiation and determined the importance of niche adaptation and divergence in these processes. We expected cladogenesis would accompany novel habitats formed by mountain uplift, but colonization would become more important with time as dispersal opportunities accrue. Location New Zealand, Southern Alps. Taxon Veronica sect. Hebe (Plantaginaceae). Methods We estimated the most complete time‐calibrated phylogeny to date for Veronica sect. Hebe to quantify rates of in situ cladogenesis and colonization of mountain habitat based on historical biogeographical models. We used environmental niche modelling to quantify species' climate niches and estimate niche disparity and divergence over time. Results In situ cladogenesis generated more species in the mountains than colonization from lowlands. Whereas cladogenesis slowed over time, colonization increased, especially in the alpine zone. Both adaptive ecological speciation along climate niche axes and non‐adaptive, vicariant speciation contributed to cladogenesis. However, climate niche disparity through time became saturated, suggesting competition for niche space was important. Colonization brought more divergent species into mountain niches. Main Conclusions We suggest mountain diversity accumulates through three main stages: high cladogenesis after initial colonization, decreasing cladogenesis with increasing competition and increasing colonization after niches saturate, likely promoted by niche divergence. Combining lineage and mountain uplift trajectories, these stages provide a conceptual model to understand how diversity accumulates elsewhere. Assuming these deep‐time findings apply to anthropogenic conditions, alpine specialists could struggle to outcompete colonizers facilitated by climate change, especially from generalist clades. Considering novel competitive interactions alongside niche traits and biogeographical processes will be crucial for predicting the fate of alpine biodiversity in a changing world.

Slow and steady wins the race: Diversification rate is independent from body size and lifestyle in Malagasy skinks (Squamata: Scincidae: Scincinae) - Francesco Belluardo; A. Jesus Muñoz-Pajares; Aurélien Miralles; Daniele Silvestro; Walter Cocca; Fanomezana Mihaja Ratsoavina; Andrea Villa; Sam Hyde Roberts; Marcello Mezzasalma; Alexander Zizka; Alexandre Antonelli; Angelica Crottini (Molecular Phylogenetics and Evolution, 2023)

Effects of Sodium Monensin on Copper Metabolism of Brazilian Santa Inês Sheep Submitted to Different Dietary Copper - Frederico Augusto Mazzocca Lopes Rodrigues; Rejane dos Santos Sousa; Antonio Humberto Hamad Minervino; Francisco Leonado Costa de Oliveira; Isadora Karolina Freitas de Sousa; Carolina Akiko Sato Cabral Araújo; Clara Satsuki Mori; Alexandre Coutinho Antonelli; Raimundo Alves Barrêto Júnior; Enrico Lippi Ortolani (Biological Trace Element Research, 2023)

Molecular taxonomic identification and species-level phylogeny of the narrow-mouthed frogs of the genus Rhombophryne (Anura: Microhylidae: Cophylinae) from Madagascar - Francesco Belluardo; Mark D. Scherz; Bárbara Santos; Franco Andreone; Alexandre Antonelli; Frank Glaw; A. Jesus Muñoz-Pajares; Jasmin E. Randrianirina; Achille P. Raselimanana; Miguel Vences; Angelica Crottini (Systematics and Biodiversity, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

The counteracting effects of anthropogenic speciation and extinction on mammal species richness and phylogenetic diversity - Søren Faurby; Rasmus Østergaard Pedersen; Jens‐Christian Svenning; Alexandre Antonelli (Global Ecology and Biogeography, 2022)
Aim Human activities are causing massive increases in extinction rates but might also lead to drastic increases in speciation rates; for example, after human‐mediated spread of species to otherwise unreachable landmasses. The long‐term net anthropogenic effects on biodiversity therefore remain uncertain. Our aim was to assess the combined anthropogenic effects of extinctions and speciations on biodiversity over geological time‐scales. Location Global. Time period Present and predicted future. Major taxa studied Terrestrial mammals. Methods We estimated known anthropogenic and predicted future extinctions based on Red List categories from the International Union for Conservation of Nature. We inferred potential anthropogenic speciations, assuming that all introductions to isolated landmasses would, over time, evolve into distinct species. We then estimated changes in regional and global species richness and phylogenetic diversity attributable to these extinctions and speciations. Results We demonstrated that if all species introduced onto new landmasses develop into new species, the number of anthropogenic speciation and extinctions eventually become similar. However, even after accounting for an anthropogenic increase in speciation, our estimates suggest recovery times for phylogenetic diversity of several millions of years. Main conclusions Our results highlight that although humans are causing drastic biodiversity losses, human‐driven speciation could eventually counterbalance these losses in species numbers, whereas phylogenetic diversity, at least within our simulation scenarios, would remain permanently reduced. This conclusion, however, requires our pressures on biodiversity to cease soon and requires us to consider geological time‐scales rather than changes over this century.

Recent and local diversification of Central American understorey palms - Ángela Cano; Fred W. Stauffer; Tobias Andermann; Isabel M. Liberal; Alexander Zizka; Christine D. Bacon; Harri Lorenzi; Camille Christe; Mats Töpel; Mathieu Perret; Alexandre Antonelli (Global Ecology and Biogeography, 2022)
Aim Central America is largely covered by hyperdiverse, yet poorly understood, rain forests. Understorey palms are diverse components of these forests, but little is known about their historical assembly. It is not clear when palms in Central America reached present diversity levels and whether most species arrived from neighbouring regions or evolved locally. We addressed these questions using the most species‐rich American palm clades indicative of rain forests. We reconstructed and compared their phylogenomic and biogeographical history with the diversification of 54 other plant lineages, to gain a better understanding of the processes that shaped the assembly of Central American rain forests. Location Central America. Time period Cretaceous to present. Major taxa studied Arecaceae: Arecoideae: Bactridinae, Chamaedoreeae, Geonomateae. Methods We sampled 218 species through fieldwork and living collections. We sequenced their genomic DNA using target sequence‐capture procedures. Using 12 calibration points, we reconstructed dated phylogenies under three approaches (multispecies coalescent, maximum likelihood and Bayesian inference), conducted biogeographical analyses (dispersal–extinction–cladogenesis) and estimated phylogenetic diversity metrics. Results Dated phylogenies revealed intense diversification in Central America from 12 Ma. Local diversification events were four times more frequent than dispersal events, and we found strong phylogenetic clustering in relationship to Central America. Main conclusions Our results suggest that most understorey palm species that characterize the Central American rain forests today evolved locally after repeated dispersal events, mostly from South America. Understorey palms in Central American rain forests diversified primarily after closure of the Central American Seaway at c . 13 Ma, suggesting that the Great American Biotic Interchange was a major trigger for plant diversification in Central American rain forests. This recent diversification contrasts with the much earlier existence of rain forest palms in neighbouring South America since c . 58 Ma. We found similar timings of diversification in 54 other seed plant lineages, suggesting an unexpectedly recent assembly of the hyperdiverse Central American flora.

Spatio‐temporal evolution of the catuaba clade in the Neotropics: Morphological shifts correlate with habitat transitions - Maria Fernanda Calió; Verônica A. Thode; Christine D. Bacon; Daniele Silvestro; Alexandre Antonelli; Lúcia G. Lohmann (Journal of Biogeography, 2022)
Aim The biotic assembly of one of the most species‐rich savannas, the Brazilian Cerrado, has involved recruitment of lineages from several surrounding regions. However, we lack a clear understanding about the timing and pathways of biotic exchanges among these regions and about the role those interchanges had in the assembly of Neotropical biodiversity. We investigated the timing and routes of species movements between wet or seasonally dry habitats across Neotropical regions and assessed the potential for ecological adaptation by evaluating the habitat transitions correlated with morphological shifts. Location Neotropics. Taxon The plant genus Anemopaegma (Bignonieae, Bignoniaceae). Methods We inferred a Bayesian molecular phylogeny of Anemopaegma using one nuclear and two chloroplast markers. We sampled more than 90% of the known species diversity of Anemopaegma , covering its full geographical range. We estimated divergence times using a Bayesian relaxed‐clock approach and inferred ancestral ranges as well as shifts in habitat and morphological characters. Results Phylogenetic analyses recovered seven main clades within Anemopaegma . The genus likely originated in Amazonia in the late Oligocene. Early‐diverging lineages diversified in situ in Amazonia, particularly during the Miocene, with independent dispersal events to the Andes, Atlantic Forest and Cerrado. Shifts from seasonally dry forest to savanna habitats were correlated with shifts from liana to shrub and the loss of tendrils. Main Conclusions The timing of diversification of major lineages within Anemopaegma is consistent with major geological and climatic events that occurred during the late Palaeogene and Neogene, such as the Andean uplift and the Middle Miocene Climatic Optimum. Movements across different regions within the Neotropics were relatively common but shifts between habitats were not. The correlation in the evolution of the shrubby habit, the loss of tendrils and the shifts from forest to savanna are consistent with a scenario of ecological adaptation.

Phylogenetic and functional clustering illustrate the roles of adaptive radiation and dispersal filtering in jointly shaping late‐Quaternary mammal assemblages on oceanic islands - Xingfeng Si; Marc W. Cadotte; T. Jonathan Davies; Alexandre Antonelli; Ping Ding; Jens‐Christian Svenning; Søren Faurby (Ecology Letters, 2022)
Islands frequently harbour unique assemblages of species, yet their ecological roles and differences are largely ignored in island biogeography studies. Here, we examine eco‐evolutionary processes structuring mammal assemblages on oceanic islands worldwide, including all extant and extinct late‐Quaternary mammal species. We find island mammal assemblages tend to be phylogenetically clustered (share more recent evolutionary histories), with clustering increasing with island area and isolation. We also observe that mammal assemblages often tend to be functionally clustered (share similar traits), but the strength of clustering is weak and generally independent from island area or isolation. These findings indicate the important roles of in situ speciation and dispersal filtering in shaping island mammal assemblages under pre‐anthropogenic conditions, notably through adaptive radiation of a few clades (e.g. bats, with generally high dispersal abilities). Our study demonstrates that considering the functional and phylogenetic axes of diversity can better reveal the eco‐evolutionary processes of island community assembly.

Certification of açaí agroforestry increases the conservation potential of the Amazonian tree flora - Gabriel Damasco; Mandy Anhalt; Ricardo O. Perdiz; Florian Wittmann; Rafael L. de Assis; Jochen Schöngart; Maria T. F. Piedade; Christine D. Bacon; Alexandre Antonelli; Paul V. A. Fine (Agroforestry Systems, 2022)
The harvesting of açaí berries (palm fruits from the genus Euterpe ) in Amazonia has increased over the last 20 years due to a high local and global market demand and triggered by their widely acclaimed health benefits as a ‘superfood’. Although such increase represents a financial boom for local communities, unregulated extraction in Amazonia risks negative environmental effects including biodiversity loss through açai intensification and deforestation. Alternatively, the introduction of certified sustainable agroforestry production programs of açaí has been strategically applied to reduce the exploitation of Amazonian forests. Local açaí producers are required to follow principles of defined sustainable management practices, environmental guidelines, and social behaviors, paying specific attention to fair trade and human rights. In this study we investigate whether sustainable agroforestry and certification effectively promotes biodiversity conservation in Amazonia. To address this question, we conducted a forestry inventory in two hectares of long-term certified açai harvesting areas to gain further knowledge on the plant diversity and forest structure in açaí managed forests and to understand the contribution of certification towards sustainable forest management. On average, we found that certified managed forests harbor 50% more tree species than non-certified açaí groves. Trees in certified areas also have significantly higher mean basal area, meaning larger and hence older individuals are more likely to be protected. Certified harvesting sites also harbor dense populations of threatened species as classified by the International Union for Conservation of Nature (e.g. Virola surinamensis, classified as ‘endangered’). Besides increasing the knowledge of plant diversity in açaí managed areas, we present baseline information for monitoring the impact of harvesting activities in natural ecosystems in Amazonia.

A bioinformatic platform to integrate target capture and whole genome sequences of various read depths for phylogenomics - Pedro G. Ribeiro; María Fernanda Torres Jiménez; Tobias Andermann; Alexandre Antonelli; Christine D. Bacon; Pável Matos‐Maraví (Molecular Ecology, 2021)
The increasing availability of short‐read whole genome sequencing (WGS) provides unprecedented opportunities to study ecological and evolutionary processes. Although loci of interest can be extracted from WGS data and combined with target sequence data, this requires suitable bioinformatic workflows. Here, we test different assembly and locus extraction strategies and implement them into secapr , a pipeline that processes short‐read data into multilocus alignments for phylogenetics and molecular ecology analyses. We integrate the processing of data from low‐coverage WGS ( k mer simultaneously for assembly results in the highest yield of extracted loci from de novo assembled contigs, while data sets derived from sequencing read depths as low as 5× recovers the expected species relationships in phylogenetic trees. By making the tested assembly approaches available in the secapr pipeline, we hope to inspire future studies to incorporate complementary data and make an informed choice on the optimal assembly strategy.

B io ‐D em , a tool to explore the relationship between biodiversity data availability and socio‐political conditions in time and space - Alexander Zizka; Oskar Rydén; Daniel Edler; Johannes Klein; Allison Perrigo; Daniele Silvestro; Sverker C. Jagers; Staffan I. Lindberg; Alexandre Antonelli (Journal of Biogeography, 2021)
Aim Geo‐referenced species occurrence records are a prime example of biodiversity data and a cornerstone of biodiversity research. Yet, their availability depends on non‐biological factors, including the political framework in the region of collection. Here we present B io ‐D em ( www.bio‐dem.surge.sh ), an open‐source software to explore the relationship between the availability of species occurrence records and the political framework in countries worldwide and through time. Location Global. Taxon Any. Methods B io ‐D em accesses the number of occurrence records available from countries worldwide from the Global Biodiversity Information Facility ( www.gbif.org ) and socio‐political information from these countries from the Varieties of Democracy database ( www.v‐dem.net ) as well as information on colonial history from the Issue Correlates of War Project. Results B io ‐D em is available as a free graphical user interface web application at www.bio‐dem.surge.sh . Through three interactive graphs, B io ‐D em enables users to explore the relationship between species occurrence records and countries’ regime type, freedom of movement, freedom of association, gross domestic product, education length, political corruption, armed conflict and colonial history. We describe possible links of these specific political indicators with the collection and mobilization of biodiversity data. Illustrative examples and video tutorials explaining the use of B io ‐D em are available at www.bio‐dem.surge.sh . Main conclusions B io ‐D em provides a user‐friendly way to explore the link between socio‐political variables and the availability of species occurrence records in user‐selected taxa and geographic regions, and to generate hypotheses on their connection. We envision B io ‐D em as a useful tool for teachers communicating the caveats of available biodiversity data, for biodiversity scientists exploring potential spatial and temporal bias in their data, and for social scientists exploring the impact of political systems on scientific data collection and biodiversity conservation.

Contrasting patterns of phylogenetic turnover in amphibians and reptiles are driven by environment and geography in Neotropical savannas - Josué A. R. Azevedo; Cristiano de C. Nogueira; Alexandre Antonelli; Søren Faurby (Journal of Biogeography, 2021)
Aim Cross‐taxonomic congruence in biodiversity patterns is key to understanding the main drivers of community structure, for biogeographical regionalization and to guide conservation. We aim to map the patterns of phylogenetic turnover and disentangle the geographical and environmental factors that drive the phylogenetic composition of distinct faunal assemblages. Location The Cerrado savannas of South America. Taxa Reptiles and amphibians. Methods We measured the proportion of phylogenetic branches shared among sites (i.e. phylogenetic turnover) using presence‐absence matrices for all species in the Cerrado and for endemics only, including only well‐sampled localities from previously compiled inventories. We then tested whether phylogenetic turnover is different from null expectations based on taxonomic turnover. We used generalized dissimilarity modelling (GDM) to test whether geography, topography, soil or climate best explain phylogenetic turnover. Finally, we mapped the observed and the GDM‐predicted clustering of phylogenetic turnover to assess geographical congruence between reptiles and amphibians. Results For all reptiles, geographical distance is the most important factor explaining phylogenetic turnover, whereas for endemic reptiles and amphibians, in general, a set of climatic variables and relief roughness are more important. We did not find any significant correlation between the phylogenetic turnover of reptiles and amphibians, as evidenced by non‐congruent phylogenetic clustering and by different responses to geographical and environmental gradients. Main conclusions The different relationships of phylogenetic turnover of reptiles and amphibians to geographical and environmental distances have ultimately shaped the phylogenetic regionalization of these two groups. This incongruence indicates the differential importance of niche filtering, dispersal limitation and the influence of neighbouring biomes in the regionalization of different groups of organisms. Therefore, diversity patterns of one group should ideally not be used as a surrogate to map general patterns or to understand the drivers of diversity of other co‐occurring groups. Thus, conservation efforts need to be designed and implemented for each organismal group.

Ten golden rules for reforestation to optimize carbon sequestration, biodiversity recovery and livelihood benefits - Alice Di Sacco; Kate A. Hardwick; David Blakesley; Pedro H. S. Brancalion; Elinor Breman; Loic Cecilio Rebola; Susan Chomba; Kingsley Dixon; Stephen Elliott; Godfrey Ruyonga; Kirsty Shaw; Paul Smith; et al. (Global Change Biology, 2021)
Urgent solutions to global climate change are needed. Ambitious tree‐planting initiatives, many already underway, aim to sequester enormous quantities of carbon to partly compensate for anthropogenic CO 2 emissions, which are a major cause of rising global temperatures. However, tree planting that is poorly planned and executed could actually increase CO 2 emissions and have long‐term, deleterious impacts on biodiversity, landscapes and livelihoods. Here, we highlight the main environmental risks of large‐scale tree planting and propose 10 golden rules, based on some of the most recent ecological research, to implement forest ecosystem restoration that maximizes rates of both carbon sequestration and biodiversity recovery while improving livelihoods. These are as follows: (1) Protect existing forest first; (2) Work together (involving all stakeholders); (3) Aim to maximize biodiversity recovery to meet multiple goals; (4) Select appropriate areas for restoration; (5) Use natural regeneration wherever possible; (6) Select species to maximize biodiversity; (7) Use resilient plant material (with appropriate genetic variability and provenance); (8) Plan ahead for infrastructure, capacity and seed supply; (9) Learn by doing (using an adaptive management approach); and (10) Make it pay (ensuring the economic sustainability of the project). We focus on the design of long‐term strategies to tackle the climate and biodiversity crises and support livelihood needs. We emphasize the role of local communities as sources of indigenous knowledge, and the benefits they could derive from successful reforestation that restores ecosystem functioning and delivers a diverse range of forest products and services. While there is no simple and universal recipe for forest restoration, it is crucial to build upon the currently growing public and private interest in this topic, to ensure interventions provide effective, long‐term carbon sinks and maximize benefits for biodiversity and people.

Trade‐off between seed dispersal in space and time - Si‐Chong Chen; Peter Poschlod; Alexandre Antonelli; Udayangani Liu; John B. Dickie (Ecology Letters, 2020)
Seed movement and delayed germination have long been thought to represent alternative risk‐spreading strategies, but current evidence covers limited scales and yields mixed results. Here we present the first global‐scale test of a negative correlation between dispersal and dormancy. The result demonstrates a strong and consistent pattern that species with dormant seeds have reduced spatial dispersal, also in the context of life‐history traits such as seed mass and plant lifespan. Long‐lived species are more likely to have large, non‐dormant seeds that are dispersed far. Our findings provide robust support for the theoretical prediction of a dispersal trade‐off between space and time, implying that a joint consideration of risk‐spreading strategies is imperative in studying plant life‐history evolution. The bet‐hedging patterns in the dispersal–dormancy correlation and the associated reproductive traits have implications for biodiversity conservation, via prediction of which plant groups would be most impacted in the changing era.

Transitions between biomes are common and directional in Bombacoideae (Malvaceae) - Alexander Zizka; Jefferson G. Carvalho‐Sobrinho; R. Toby Pennington; Luciano P. Queiroz; Suzana Alcantara; David A. Baum; Christine D. Bacon; Alexandre Antonelli (Journal of Biogeography, 2020)
Aim To quantify evolutionary transitions between tropical evergreen rain forest and seasonally dry biomes, to test whether biome transitions affect lineage diversification and to examine the robustness of these results to methodological choices. Location The tropics. Time period The Cenozoic. Major taxa studied The plant subfamily Bombacoideae (Malvaceae). Methods We inferred ancestral biomes based on a fossil‐dated molecular phylogeny of 103 species (59% of the clade) and recorded the number of transitions among biomes using biogeographical stochastic mapping based on the dispersal‐extinction‐cladogenesis model. We then estimated diversification rates using state‐specific speciation and extinction rate ( SSE ) methods. Furthermore, we tested the sensitivity of the results to model choice, phylogenetic uncertainty, measurement error and biome definition. Results We found numerous transitions from evergreen rain forest to seasonally dry biomes, and fewer in the opposite direction. These results were robust to methodological choices. Biome type did not influence diversification rates, although this result was subject to uncertainty, especially related to model choice and biome definition. Main conclusions Our results contradict the idea of evolutionary biome conservatism in Bombacoideae, and support previous findings that evergreen rain forests serve as a source for the flora of seasonally dry biomes. The impact of biome classification and biome definition on the results suggest caution when using a biome concept for biogeographical reconstruction and diversification rate analysis.

Brain expansion in early hominins predicts carnivore extinctions in East Africa - Søren Faurby; Daniele Silvestro; Lars Werdelin; Alexandre Antonelli (Ecology Letters, 2020)
While the anthropogenic impact on ecosystems today is evident, it remains unclear if the detrimental effect of hominins on co‐occurring biodiversity is a recent phenomenon or has also been the pattern for earlier hominin species. We test this using the East African carnivore fossil record. We analyse the diversity of carnivores over the last four million years and investigate whether any decline is related to an increase in hominin cognitive capacity, vegetation changes or climatic changes. We find that extinction rates in large carnivores correlate with increased hominin brain size and with vegetation changes, but not with precipitation or temperature changes. While temporal analyses cannot distinguish between the effects of vegetation changes and hominins, we show through spatial analyses of contemporary carnivores in Africa that only hominin causation is plausible. Our results suggest that substantial anthropogenic influence on biodiversity started millions of years earlier than currently assumed.

Linking democracy and biodiversity conservation: Empirical evidence and research gaps - Oskar Rydén; Alexander Zizka; Sverker C. Jagers; Staffan I. Lindberg; Alexandre Antonelli (Ambio, 2020)

Why mountains matter for biodiversity - Allison Perrigo; Carina Hoorn; Alexandre Antonelli (Journal of Biogeography, 2020)
Mountains are arguably Earth's most striking features. They play a major role in determining global and regional climates, are the source of most rivers, act as cradles, barriers and bridges for species, and are crucial for the survival and sustainability of many human societies. The complexity of mountains is tightly associated with high biodiversity, but the processes underlying this association are poorly known. Solving this puzzle requires researchers to generate more primary data, and better integrate available geological and climatic data into biological models of diversity and evolution. In this perspective, we highlight emerging insights, which stress the importance of mountain building through time as a generator and reservoir of biodiversity. We also discuss recently proposed parallels between surface uplift, habitat formation and species diversification. We exemplify these links and discuss other factors, such as Quaternary climatic variations, which may have obscured some mountain‐building evidence due to erosion and other processes. Biological evolution is complex and the build‐up of mountains is certainly not the only explanation, but biological and geological processes are probably more intertwined than many of us realize. The overall conclusion is that geology sets the stage for speciation, where ecological interactions, adaptive and non‐adaptive radiations and stochastic processes act together to increase biodiversity. Further integration of these fields may yield novel and robust insights.

The effects of climate change on the distribution of South American antbirds (Thamnophilus punctatus complex) as affected by niche divergences and contact zone interactions between species - Erasmo Andrade da Silva; Helder Farias Pereira de Araujo; Alexandre Aleixo; Alexandre Antonelli; Alexandre M. Fernandes (Journal of Ornithology, 2020)

Drivers of bromeliad leaf and floral bract variation across a latitudinal gradient in the Atlantic Forest - Beatriz Neves; Camila M. Zanella; Igor M. Kessous; Fernando P. Uribbe; Fabiano Salgueiro; Fernanda Bered; Alexandre Antonelli; Christine D. Bacon; Andrea F. Costa (Journal of Biogeography, 2020)
Aim Understanding the complex interaction and relative contributions of factors involved in species and trait diversification is crucial to gain insights into the evolution of Neotropical biodiversity. Here, we investigated the drivers of morphological variation in bromeliads along a latitudinal gradient in a biodiversity hotspot. Location Atlantic Forest, Brazil. Taxon A species complex in the genus Vriesea (Bromeliaceae). Methods We measured shape and size variation for 208 floral bracts and 176 leaves in individuals from 14 localities using geometric morphometrics. We compiled data for two chloroplast regions ( matK and trnL‐F ) from 89 individuals to assess genetic diversity, population structure and phylogenetic relationships. We tested the influence of climate, altitude and genetic distance on morphological traits using linear statistical models. Results Temperature seasonality is a main driver of floral bract shape. Together with precipitation, it also explains changes in leaf size across the latitudinal gradient. Shifts in morphological traits are correlated with genetic structure and partly support the recent taxonomic delimitation proposed for the species complex. The species started to diversify in the Pliocene ca. 5 Mya. We detected a phylogeographical break in species distribution into northern and southern clades between the Bocaina region and the southern portion of the Atlantic Forest. Main Conclusions We identify how geography and environmental changes through time shape floral bracts and leaves in similar ways. At highly seasonal sites with lower annual precipitation (in the southern subtropical portion of the Atlantic Forest), leaves are larger and floral bracts are wide‐elliptic, making them better suited for increased water accumulation. In contrast, at less seasonal sites (in the tropical north, where rainfall is more abundant and temperatures are higher), leaves are narrower and floral bracts are lanceolate‐shaped, facilitating water drainage. The biogeographical break we identified suggests a role of tectonic activity and climatic oscillations in promoting species divergence and diversification.

Could coastal plants in western Amazonia be relicts of past marine incursions? - Rodrigo Bernal; Christine D. Bacon; Henrik Balslev; Carina Hoorn; Sarah J. Bourlat; Hanna Tuomisto; Sonia Salamanca; Milan Teunissen van Manen; Ingrid Romero; Pierre Sepulchre; Alexandre Antonelli (Journal of Biogeography, 2019)
The rainforests of Amazonia comprise some of the most biologically diverse ecosystems on Earth. Despite this high biodiversity, little is known about how landscape changes that took place in deep history have affected the assembly of its species, and whether the impact of such changes on biodiversity can still be observed. Here, we present a hypothesis to explain our observation that plants typical of Neotropical coastal habitats also occur in western Amazonia, in some cases thousands of kilometres away from the coast. Evidence on their current distribution, dispersal biology and divergence times estimated from molecular phylogenies suggest that these plants may be the legacy of the large marine‐influenced embayment that dominated the area for millions of years in the Neogene. We hypothesize that coastal plants dispersed along the shores of this embayment and persisted as inland relicts after the marine incursion(s) retreated, probably with the aid of changes in soil conditions caused by the deposition of marine sediments. This dispersal corridor may also have facilitated the colonization of coastal environments by Amazonian lineages. These scenarios could imply an unexpected coastal source that has contributed to Amazonia's high floristic diversity and led to disjunct distributions across the Neotropics. We highlight the need for future studies and additional evidence to validate and shed further light on this potentially important pattern.

Human activity is altering the world’s zoogeographical regions - Rubén Bernardo‐Madrid; Joaquín Calatayud; Manuela González‐Suárez; Martin Rosvall; Pablo M. Lucas; Marta Rueda; Alexandre Antonelli; Eloy Revilla (Ecology Letters, 2019)
Zoogeographical regions, or zooregions, are areas of the Earth defined by species pools that reflect ecological, historical and evolutionary processes acting over millions of years. Consequently, researchers have assumed that zooregions are robust and unlikely to change on a human timescale. However, the increasing number of human‐mediated introductions and extinctions can challenge this assumption. By delineating zooregions with a network‐based algorithm, here we show that introductions and extinctions are altering the zooregions we know today. Introductions are homogenising the Eurasian and African mammal zooregions and also triggering less intuitive effects in birds and amphibians, such as dividing and redefining zooregions representing the Old and New World. Furthermore, these Old and New World amphibian zooregions are no longer detected when considering introductions plus extinctions of the most threatened species. Our findings highlight the profound and far‐reaching impact of human activity and call for identifying and protecting the uniqueness of biotic assemblages.

Evolutionary and ecological success is decoupled in mammals - Søren Faurby; Alexandre Antonelli (Journal of Biogeography, 2018)
Aim To identify which factors distinguish ecologically successful mammalian clades (i.e., clades with a large combined range size) from less successful ones. Location Global. Methods We estimated the total range sizes for each individual mammalian subfamily and used phylogenetic regressions to identify the relative importance of factors related to colonization ability (body size and niche width) and adaptability (rate of evolution of body size and rate of evolution of climatic preference) in determining these ranges. We then estimated the importance of the same factors on the variation in diversification rate within mammals. Results We found strong support for a link between total range size and traits related to colonization ability. In particular, we found larger total range sizes among clades containing larger bodied species and clades with wider climatic niche width, while we did not find support for any predictors related to adaptability being linked to total range size. We also found that traits related to increased range size were associated with reduced diversification rate. Main Conclusions Range size for mammalian clades is mainly predicted by colonization ability, suggesting that most clades are limited by dispersal rather than their ability to adapt to new environments. The most ecologically successful (i.e., most widespread) mammalian clades tend to possess traits that reduce geographical isolation among populations, but the same traits tend to decrease diversification rates. Our results unveil a decoupling between evolutionary and ecological success in mammals.

Iriarteeae palms tracked the uplift of Andean Cordilleras - Christine D. Bacon; Francisco J. Velásquez‐Puentes; Carina Hoorn; Alexandre Antonelli (Journal of Biogeography, 2018)
Aim The high biodiversity of northern South America is unparalleled and includes several centres of diversity such as Amazonia, the Andes and the Chocó. Movement of lineages amongst and within these bioregions is thought to be rare, and the effect of those dispersals on the distribution, diversity, and community assembly remains poorly understood. Here we address these effects by studying divergence times, biogeographical history, and species diversification of the palm tribe Iriarteeae, an ecologically dominant forest component. Location Central and South America. Methods We developed a calibrated phylogeny and a spatially explicit diversification model that incorporates molecular and fossil data. In these analyses, we included a new fossil Iriartea species Gemmamonocolpites galeanoana , derived from new samples of Miocene deposits in western Amazonia. We also estimated the geographical range evolution of lineages and tested whether speciation and extinction rates were affected by dispersal events using a simulation approach in Cla SSE . Results Dispersal amongst bioregions was not evenly distributed across the topology. We found that Amazonian communities are overdispersed across the phylogeny, whereas Andean taxa are clustered. Dispersal events were associated with increases in species diversification and were concomitant with periods of Andean uplift. Migration into montane areas occurred several times from lowland Amazonian ancestors, and montane taxa subsequently recolonized the Amazonian bioregion. Main conclusions Our results suggest that the diversification of Iriarteeae palms closely followed the west‐to‐east surface uplift history of the Northern Andes. From an early, lowland Amazonian ancestor, the first diversification events took place in the earliest emerging mountain chain, the Western Cordillera. From there multiple range expansions followed eastwards and back into the lowlands. This study demonstrates how geological events within a single mountain range can affect the geographical expansion and diversification of lineages.

The roles of dispersal and mass extinction in shaping palm diversity across the Caribbean - Ángela Cano; Christine D. Bacon; Fred W. Stauffer; Alexandre Antonelli; Martha L. Serrano‐Serrano; Mathieu Perret (Journal of Biogeography, 2018)
Aim The rich flora of the Caribbean islands and surrounding mainland evolved in a context of isolation alternated with phases of terrestrial connectivity between landmasses, climatic fluctuations and episodes of mass extinctions during the Cenozoic. We explored how these events affected the evolution of the sister palm tribes Cryosophileae and Sabaleae, and how continent‐island exchanges, endemic radiations and mass extinction shaped their extant diversity. Location The American continent including the Caribbean region. Methods We reconstructed a time‐calibrated phylogeny of the palm tribes Cryosophileae and Sabaleae using 84% of the known species. We inferred ancestral distribution and tested the effect of island colonization and mass extinction on extant diversity. Results Our results indicate that Cryosophileae and Sabaleae originated c . 77 Ma most probably in Laurasia, and their extant species started to diversify between 56–35 Ma and 19–10 Ma respectively. Biogeographical state reconstruction estimated that Cryosophileae dispersed to South America between 56–35 Ma, then dispersed to North‐Central America between 39–25 Ma and the Caribbean islands between 34–21 Ma. We detected a possible signature of a mass extinction event at the end of the Eocene, affecting the diversification of Cryosophileae and Sabaleae and we did not detect a diversification rate shift related to the colonization of the Caribbean islands. Main conclusions Species of Cryosophileae in the Caribbean islands are probably derived from a single Oligocene dispersal event that likely occurred overwater from North‐Central America rather than through the hypothesized GAAR landia land bridge. Contrastingly, three independent Miocene dispersal events from North‐Central America explain the occurrence of Sabaleae in the Caribbean islands. Contrary to our expectations, island colonization did not trigger increased diversification. Instead, we find that diversification patterns in this clade, and its disappearance from northernmost latitudes, could be the signature of a mass extinction triggered by the global temperature decline at the end of the Eocene.

The impact of early Quaternary climate change on the diversification and population dynamics of a South American cactus species - Gislaine Angélica Rodrigues Silva; Alexandre Antonelli; Anita Lendel; Evandro de Marsola Moraes; Maura Helena Manfrin (Journal of Biogeography, 2018)
Aim Climatic oscillations have been suggested to promote speciation and changes in species distributions, mostly in connection with the Last Glacial Maximum ( LGM ). However, the LGM is just the most recent of the 20+ glacial‐interglacial periods that characterise the Quaternary. Here, we investigate the role of climatic changes and geomorphological features in shaping the evolution, distribution and population dynamics of the South American cactus Cereus hildmannianus . Location South‐eastern South America. Methods We built a large fossil‐calibrated phylogeny for cacti (family Cactaceae), comprising 128 species distributed in all subfamilies, using a Bayesian relaxed clock. We used the results to derive a secondary calibration for a population‐level phylogeny in C. hildmannianus . We amplified two plastid ( trnQ‐5′rps16 and psbJ‐petA ) and one nuclear marker ( PhyC ) for 24 populations. We estimated population dynamics, ancestral areas, and species distribution models to infer the clade's evolutionary history in time and space. Results Our results show a major population divergence of C. hildmannianus at c . 2.60 Ma, which is strikingly coincident with the transition of the Pliocene–Pleistocene and onset of Quaternary glaciations. This was followed by a complex phylogeographic scenario involving population expansions across ecologically diverse regions. Main conclusions Contrary to the dominant research focus on the LGM , our study indicates a major impact of the first Quaternary glaciation on the distribution and population divergence of a South American plant species. Further intraspecific events seem related to successive climatic changes and geomorphology, including the development of the coastal plain and its peculiar diversity. We propose that the first Quaternary glaciation acted as a major evolutionary bottleneck, whereby many warm‐adapted lineages succumbed, while those that survived could diversify and better cope with subsequent climatic oscillations.

Patterns, biases and prospects in the distribution and diversity of Neotropical snakes - Thaís B. Guedes; Ricardo J. Sawaya; Alexander Zizka; Shawn Laffan; Søren Faurby; R. Alexander Pyron; Renato S. Bérnils; Martin Jansen; Paulo Passos; Ana L. C. Prudente; Diego F. Cisneros‐Heredia; Henrique B. Braz; et al. (Global Ecology and Biogeography, 2018)
Motivation We generated a novel database of Neotropical snakes (one of the world's richest herpetofauna) combining the most comprehensive, manually compiled distribution dataset with publicly available data. We assess, for the first time, the diversity patterns for all Neotropical snakes as well as sampling density and sampling biases. Main types of variables contained We compiled three databases of species occurrences: a dataset downloaded from the Global Biodiversity Information Facility (GBIF), a verified dataset built through taxonomic work and specialized literature, and a combined dataset comprising a cleaned version of the GBIF dataset merged with the verified dataset. Spatial location and grain Neotropics, Behrmann projection equivalent to 1° × 1°. Time period Specimens housed in museums during the last 150 years. Major taxa studied Squamata: Serpentes. Software format Geographical information system (GIS). Results The combined dataset provides the most comprehensive distribution database for Neotropical snakes to date. It contains 147,515 records for 886 species across 12 families, representing 74% of all species of snakes, spanning 27 countries in the Americas. Species richness and phylogenetic diversity show overall similar patterns. Amazonia is the least sampled Neotropical region, whereas most well‐sampled sites are located near large universities and scientific collections. We provide a list and updated maps of geographical distribution of all snake species surveyed. Main conclusions The biodiversity metrics of Neotropical snakes reflect patterns previously documented for other vertebrates, suggesting that similar factors may determine the diversity of both ectothermic and endothermic animals. We suggest conservation strategies for high‐diversity areas and sampling efforts be directed towards Amazonia and poorly known species.

Estimating species diversity and distribution in the era of B ig D ata: to what extent can we trust public databases? - Carla Maldonado; Carlos I. Molina; Alexander Zizka; Claes Persson; Charlotte M. Taylor; Joaquina Albán; Eder Chilquillo; Nina Rønsted; Alexandre Antonelli (Global Ecology and Biogeography, 2015)
Aim Massive digitalization of natural history collections is now leading to a steep accumulation of publicly available species distribution data. However, taxonomic errors and geographical uncertainty of species occurrence records are now acknowledged by the scientific community – putting into question to what extent such data can be used to unveil correct patterns of biodiversity and distribution. We explore this question through quantitative and qualitative analyses of uncleaned versus manually verified datasets of species distribution records across different spatial scales. Location The A merican tropics. Methods As test case we used the plant tribe C inchoneae ( R ubiaceae). We compiled four datasets of species occurrences: one created manually and verified through classical taxonomic work, and the rest derived from GBIF under different cleaning and filling schemes. We used new bioinformatic tools to code species into grids, ecoregions, and biomes following WWF's classification. We analysed species richness and altitudinal ranges of the species. Results Altitudinal ranges for species and genera were correctly inferred even without manual data cleaning and filling. However, erroneous records affected spatial patterns of species richness. They led to an overestimation of species richness in certain areas outside the centres of diversity in the clade. The location of many of these areas comprised the geographical midpoint of countries and political subdivisions, assigned long after the specimens had been collected. Main conclusion Open databases and integrative bioinformatic tools allow a rapid approximation of large‐scale patterns of biodiversity across space and altitudinal ranges. We found that geographic inaccuracy affects diversity patterns more than taxonomic uncertainties, often leading to false positives, i.e. overestimating species richness in relatively species poor regions. Public databases for species distribution are valuable and should be more explored, but under scrutiny and validation by taxonomic experts. We suggest that database managers implement easy ways of community feedback on data quality.

Disentangling the influence of climatic and geological changes on species radiations - H. Peter Linder; Daniel L. Rabosky; Alexandre Antonelli; Rafael O. Wüest; Ralf Ohlemüller (Journal of Biogeography, 2014)
Aim Our aim was to seek explanations for the differences in the diversity among the austral continents by comparing the diversification rates and patterns in the grass subfamily Danthonioideae. We asked specifically whether diversification is density dependent, whether it is different for each continent, and whether immigration rates impact on diversification rates. We attempted to account for intercontinental differences by comparing the Pleistocene climatic and Neogene geomorphological histories with the inferred diversification rates. Location Mainly the Southern Hemisphere, treated as four areas for the analyses: Africa, Australia, New Zealand and South America. Methods We based our analyses on a densely sampled, dated phylogeny for the grass subfamily Danthonioideae. We compared 24 diversification models for these continental radiations, taking into account speciation models, and extinction and dispersal rates. We used available distribution data to infer the climates under which danthonioids are found, and used these to estimate the change in area and location of suitable habitats between contemporary and Last Glacial Maximum climates. We inferred the geomorphological history from the literature. Results We show that long‐distance dispersal led to parallel radiations, which more than doubled the final standing diversity in the subfamily. Diversification models with the strongest support included separate time‐varying diversification processes for each major geographical region. Pleistocene climatic fluctuation did not explain the intercontinental differences in diversification patterns. Main conclusions Although our results are consistent with density‐dependent diversification, this explanation is not consistent with the time of arrival of danthonioids on each continent. The diversification patterns on the four major Southern Hemisphere landmasses are idiosyncratic. The two most important predictors of diversity may be the lineage‐specific effect of time, and the general effect of topographical complexity and orogenesis.

What determines biogeographical ranges? Historical wanderings and ecological constraints in the danthonioid grasses - H. Peter Linder; Alexandre Antonelli; Aelys M. Humphreys; Michael D. Pirie; Rafael O. Wüest (Journal of Biogeography, 2013)
Aim We sought to understand the variables that limit the distribution range of a clade (here the danthonioid grasses). We tested time, area of origin, habitat suitability, disjunction width and nature, and wind direction as possible range determinants. Location Global, but predominantly the Southern Hemisphere. Methods We mapped the range of the subfamily Danthonioideae, and used 39,000 locality records and an ensemble modelling approach to define areas with suitable danthonioid habitat. We used a well‐sampled, dated phylogeny to estimate the number and direction of historical dispersal events, based on parsimony optimization. We tested for the impact of wind direction on dispersal rate using a likelihood approach, and for the effects of barrier width with a regression approach. Results We found 17 geographically isolated areas with suitable habitats for danthonioids. All currently suitable Southern Hemisphere areas have been occupied, but three apparently suitable areas in the Northern Hemisphere have not. We infer that southern Africa was first occupied in the Oligocene and that dispersal to the other areas was initiated in the middle Miocene. Inferred dispersal rate was correlated with the width of the disjunctions, up to a distance of 5000 km. There was no support for wind direction having influenced differences in dispersal rate. Main conclusions The current range of the Danthonioideae can be predicted ecologically (areas with suitable habitat) and historically (the width of the disjunctions separating the areas with suitable habitat and the area of origin). The direction of dispersal is dictated by the area of origin and by serendipity: there is no evidence for general patterns of dispersal, for example for dispersal occurring more frequently over land than over sea or in an easterly versus a westerly direction around the Southern Hemisphere. Thus the range and range‐filling of Danthonioideae can be accounted for by surprisingly few variables: habitat suitability, distance between suitable areas, and area of origin.

Placement of Kuhlmanniodendron Fiaschi & Groppo in Lindackerieae (Achariaceae, Malpighiales) confirmed by analyses of rbcL sequences, with notes on pollen morphology and wood anatomy - Milton Groppo; Pedro Fiaschi; Maria Luiza Faria Salatino; Gregório Cardoso Tápias Ceccantini; Francisco de Assis Ribeiro dos Santos; Christiano Franco Verola; Alexandre Antonelli (Plant Systematics and Evolution, 2010)

Brazil Should Facilitate Research Permits - Alexandre Antonelli; Victor Rodriguez (Conservation Biology, 2009)